Assessment of Telemedicine and Digital Health in Comprehensive Medical Care - Carlos Antonio Escobar Suárez; Freddy Fernando Jumbo Salazar; Iruma Alfonso González (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2024)
Due to the COVID-19 pandemic, telemedicine has seen a significant boom in employment and an undeniable impact, on healthcare. The objective of the present review was to assess the role that telemedicine and digital health play in comprehensive medical care. The authors relied on hermeneutics to analyze and evaluate the systematic review carried out with the PRISMA 2020 methodology on telemedicine and digital health. Finally, 9 articles were reviewed in the Pubmed database corresponding to the period from 2019 to 2023. The results highlight the growing importance of information and communications technologies in the context of medical care, mainly in the field of the COVID-19 pandemic. This pandemic has driven the adoption of telemedicine and technologies in healthcare, but efforts are required to ensure equity in their implementation.